2020
DOI: 10.1186/s13018-020-1551-9
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of PI3K/Akt pathway on human nucleus pulposus mesenchymal stem cells against hypoxia and nutrition deficiency

Abstract: Background: To study the effects of hypoxia and nutrition deficiency mimicking degenerated intervertebral disc on the biological behavior of human nucleus-derived pulposus mesenchymal stem cells (hNP-MSCs) and the role of PI3K/Akt pathway in the process in vitro. Methods: hP-MSCs were isolated from lumbar disc and were further identified by their immunophenotypes and multilineage differentiation. Then, cells were divided into the control group, hypoxia and nutrition deficiency group, the LY294002 group, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
(40 reference statements)
0
23
0
1
Order By: Relevance
“…Consistently, IGF-1 significantly decreased Col-X and LY294002 increased Col-X. Tian et al showed that in anoxic and nutritionally deprived environments, the Col-II gene expression significantly reduced which IGF-1 almost helped return to the normal and LY294002 worsened the situation in NP mesenchymal stem cells [ 28 ]. Our study confirmed that in normal conditions, NPCs also lose Col-II and obtain Col-X due to antagonizing P13K/AKT pathway.…”
Section: Discussionmentioning
confidence: 95%
“…Consistently, IGF-1 significantly decreased Col-X and LY294002 increased Col-X. Tian et al showed that in anoxic and nutritionally deprived environments, the Col-II gene expression significantly reduced which IGF-1 almost helped return to the normal and LY294002 worsened the situation in NP mesenchymal stem cells [ 28 ]. Our study confirmed that in normal conditions, NPCs also lose Col-II and obtain Col-X due to antagonizing P13K/AKT pathway.…”
Section: Discussionmentioning
confidence: 95%
“…For example, under oxidative damage, Resveratrol increased ECM synthesis of NPCs by enhancing autophagy through PI3K/AKT pathway [28] . Further study con rmed that PI3K/AKT pathway had protective effects on human nucleus pulposus-derived mesenchymal stem cells under hypoxia and nutrition de ciency [29] . Conversely, PTEN, the only known lipid phosphatase counteracting the PI3K/AKT pathway, promoted intervertebral disc degeneration by regulating nucleus pulposus cell behaviors [30] .…”
Section: 2mentioning
confidence: 88%
“…NPMSCs are the precursor of NPCs, which exist in healthy and degenerative IVD tissues, and has the potential to proliferate and differentiate into NPCs [ 17 ]. Furthermore, these cells show great potential for application in regenerative and repairing sciences [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%